Pilot study of long-term anaesthesia in broiler chickens - O'Kane, Peter M.; Connerton, Ian F.; White, Kate L. (Wiley, 2016)
Objective: To provide stable anaesthesia of long duration in broiler chickens in order to perform a terminal caecal ligated loop procedure.